Effect of Sitagliptin on serum adiponectin levels in type 2 diabetic patients and the relationship with Body Mass Index - البهلول علا; لينا صقر; ربا سلمان (Latakia University Journal -Medical Sciences Series, 2023)
The prevalence of type 2 diabetes mellitus around the world has greatly worsened during the last two decades, infection with this disease leads to the development of many serious complications over time, at the level of both small and large blood vessels. Insulin resistance plays a major role in the development of type 2 diabetes and Reducing this resistance is a therapeutic strategy aimed at limiting the progression of type 2 diabetes and other metabolic disorders which are associated with this resistance. Adipose tissue plays a role as a metabolically active endocrine gland through the secretion of a group of mediators called adipokines, including adiponectin, which has properties that increase tissue sensitivity to insulin Thus, the search for compounds that increase the levels of this adipokine may be a new therapeutic tool to reduce the development of diseases associated with insulin resistance. Multiple studies have been conducted to investigate the effect of sitagliptin, a member of the group of DPP-4 inhibitors, on adiponectin, but the results were inconsistent. Therefore, in this study, we examined the effect of sitagliptin on serum adiponectin levels. The study was conducted on a number of patients with type 2 diabetes attending the Endocrinology Clinic at Tishreen University Hospital. They were distributed into two groups: First group (the control group) included newly diagnosed patients who received metformin treatment, whereas the second group (the sitagliptin group), included patients diagnosed previously with type 2 diabetes for a period of 3 months or more, who were undergoing treatment with metformin, then sitagliptin was added to their treatment plan. the follow-up period lasted for 3 months. Fasting blood glucose, glycated hemoglobin, body mass index, and plasma adiponectin levels were measured. At the end of the study, a statistically significant increase in adiponectin levels was observed in both groups, and this increase was higher in metformin group (the control group) without statistically significant difference between the two groups. Therefore, the addition of sitagliptin to the treatment plan as an add-on therapy to metformin leads to an improvement in glucose control, but it does not play a significant role in raising serum adiponectin levels compared to treatment by metformin alone. On the other hand, this study showed that the addition of sitagliptin as an add-on therapy to metformin in (sitagliptin group) led to an increase in serum levels of adiponectin, and this increase was greater and statistically significant in patients with BMI (≥30 kg/m²) compared to patients with BMI (<30 kg/m²), and this statistical significance appeared in (sitagliptin group) only. without observing any significant statistical difference in (control group).